GOAT induced ghrelin acylation regulates hedonic feeding - Davis, Fernando Javier (2012)
Ghrelin is an orexigenic hormone that regulates homeostatic and reward-related feeding behavior. Recent evidence indicates that acylation of ghrelin by the gut enzyme ghrelin O-acyl transferase (GOAT) is necessary to render ghrelin maximally active within its target tissues. Here we tested the hypothesis that GOAT activity modulates food motivation and food hedonics using behavioral pharmacology and mutant mice deficient for GOAT and the ghrelin receptor (GHSR). We evaluated operant responding following pharmacological administration of acyl-ghrelin and assessed the necessity of endogenous GOAT activity for operant responding in GOAT and GHSR-null mice. Hedonic-based feeding behavior also was examined in GOAT-KO and GHSR-null mice using a "Dessert Effect" protocol in which the intake of a palatable high fat diet "dessert" was assessed in calorically-sated mice. Pharmacological administration of acyl-ghrelin augmented operant responding; notably, this effect was dependent on intact GHSR signaling. GOAT-KO mice displayed attenuated operant responding and decreased hedonic feeding relative to controls. These behavioral results correlated with decreased expression of the orexin-1 receptor in reward-related brain regions in GOAT-KO mice. In summary, the ability of ghrelin to stimulate food motivation is dependent on intact GHSR signaling and modified by endogenous GOAT activity. Furthermore, GOAT activity is required for hedonic feeding behavior, an effect potentially mediated by forebrain orexin signaling. These data highlight the significance of the GOAT-ghrelin system for the mediation of food motivation and hedonic feeding. © 2012 Elsevier Inc.